KORDUR: TIDELINE - Božanić Pepe Kalofot, Ante; Zanchi, Željka (Transactions on Maritime Science, 2023)
In this issue we present a poem by Ante Božanić (Tonko Božanić Pepe - Kalafot), a versatile artist: carpenter, ship-builder, wood-carver, performer, and poet from Komiža, Island of Vis, whose poetry we have already brought on a few occasions. We hereby continue our adherence to the traditional Croatian poets’ promotion, in an attempt to preserve the still living Dalmatian idiom. The poem has been selected and the lyrics translated by Željka Zanchi, our former colleague and long-standing collaborator.